Effects of household-level attributes and agricultural land-use on deforestation patterns along a forest transition gradient in the Miombo landscapes, Zambia - Kazungu, M.; Velasco, R.F.; Zhunusova, E.; Lippe, M.; Kabwe, G.; Gumbo, D.J.; Günter, S. (Elsevier, 2021)
Dry forests in tropical and subtropical areas continue to experience high deforestation rates that affect households' dependence on forest resources. Little remains understood about the relationship between household factors and deforestation patterns in Zambia. We integrate remotely sensed data with surveys of 1123 households collected in the Miombo areas between 2017 and 2019 to better understand the effects of household attributes on regional deforestation patterns along a forest transition gradient. We found, in early-to-mid-transition, deforestation patterns systematically decreased further from settlements (homesteads), but this was reversed in regions with advanced forest transition. The socio-demographic attributes, land and non-land-based attributes, and location factors differently affected deforestation across provinces. Although agricultural land-use was significantly associated with deforestation, no distinct patterns emerged across distance categories or along the forest transition. Furthermore, increases in non-farm income reduced the likelihood of high deforestation, but the impact was not always significant across provinces. Our results indicate that economic effects of distance in Miombo areas complement the forest transition, but are not exclusively related to crop productivity. We assume that different aspects of livelihoods can explain the deforestation patterns in the Miombo areas. Thus, forest management should be regional-specific, such as improving access to financial incentives in North-Western, and reforestation and agroforestry in Copperbelt and the Eastern Province.